The Role of Community Engagement in the Actualization of Ecological Citizenship: A Case Study of Riverbank Areas in Banjarmasin City - Riko Naufal Pebrianto; Yayuk Hidayah (Riviera Publishing, 2025)
This study applies Light’s theory of ecological citizenship which emphasizes three key aspects including responsibility for environmental impact, concern for the well-being of others, and efforts to preserve ecological sustainability. The research aims to examine how ecological citizenship is actualized in the daily lives of riverbank residents and how the local government supports this process. It employs a qualitative case study method with data collected through field observations and interviews involving 32 informants consisting of urban village heads, neighborhood leaders, and residents. Supporting literature and administrative documents were used as secondary sources, and data validation was conducted using triangulation of techniques and sources. The findings show that ecological citizenship in the riverbank areas of North Banjarmasin is reflected in both community participation and government involvement. Residents engage in waste management, voluntary clean-up efforts, and collective sanitation funding, all of which are supported by strong social cohesion. The local government contributes by providing infrastructure, organizing awareness programs, and maintaining sanitation through routine institutional initiatives. To further strengthen ecological citizenship, residents are encouraged to participate in environmental decision-making through public forums and direct communication with authorities. Local governments are advised to facilitate inclusive and informative discussion spaces, use digital platforms to broaden public engagement, and collaborate with universities and community organizations to enhance environmental education. These efforts are essential for fostering a collective sense of ecological responsibility and promoting sustainable practices in riverbank communities.